Sublethal Effects of Three Ectoparasites on Fish - Vaughan, Gene E. (University of Wisconsin-Stevens Point, 1973)
In an attempt to determine sublethal effects of parasites on fish, vulnerability-to predation, resistance to high temperature, weight-length relationships, and fecundity were compared for fish with and without or with light and heavy infestations of three ectoparasites. Species used were fathead minnow (Pimephales promelas) with anchor worm (Lernaea cyprinaceae) infestation levels ranging from 0 to 4 with a mean of 1.2 parasites per fish, brook trout (Salvelinus fontinalis) infested with gill lice (Salmincola edwardsii) at levels of 0 to J2 lice per fish with a mean of 4.1, and yellow perch (Perea flavescens) with black-spot (Neascus of Crassiphiala bulboglossa) with a range of 0 to 6JJ cysts per fish and a mean of 249. The only sublethal effect found was that of gill lice, which reduced resistance of brook trout to high temperature. None of the three actoparasites increased vulnerability of fish to predation by piscivorous fish. Weight-length relationships were the same in natural populations of brook trout with and without gill lice and in two groups of yellow perch, one with a light and one with a heavy infestation of black-spot. Fecundity of brook trout was not affected by gill lice.